APPLICATION OF THE PROBLEM BASED LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES ON HOW WE LIVE AND GROW IN CLASS V OF SD NEGERI MASJID LHEU ACEH BESAR - Handayani, Sri Meli; Fauzi, Fauzi; Fitriani, Suci (Elementary Education Research, 2025)
Problem Based Learning or what is often called PBL is a learning model that is student-centered by confronting students with various problems they face in their lives. The aim of this PTK is to describe and analyze improvements in student learning outcomes on the material of how we live and grow through the Problem Bassed Learning model for fifth grade students at SD Negeri Mesjid Lheu. The subjects in this research were 30 students. The data collection techniques used are observation and tests. Data analysis uses qualitative descriptive analysis using the percentage formula. The results of the data analysis carried out showed that there was an increase in teacher activity in managing learning in cycle I, getting an average score of 2.5 with good criteria, cycle II got an average score of 3.4 with very good criteria. Student activity in learning showed an increase in cycle I with an average score of 42.14 with sufficient criteria, in cycle II the average score was 78.57 with good criteria. Student learning outcomes show an increase, this is shown by the average value of the first cycle test results of 71.87, the second cycle of 91.2, this increase has reached the complete indicator. The use of the PBL model can increase the activities and learning outcomes of fifth grade students at Mesjid Lheu State Elementary School on the subject of how we live and grow. The application of the PBL model to science learning material about how we live and grow provides meaningful learning because students learn to understand the concept of how we live and grow.